2003
DOI: 10.1021/la011706p
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering of 4-Aminothiophenol in Assemblies of Nanosized Particles and the Macroscopic Surface of Silver

Abstract: Assemblies consisting of nanosized silver particles, 4-aminothiophenol, and the smooth macroscopic surface of silver metal (Ag/PATP/Ag) were prepared and characterized by surface-enhanced Raman spectroscopy. The Raman spectrum of 4-aminothiophenol in the assemblies is similar to that obtained on the electrochemically roughened electrode, although spectral differences, including slight frequency shifts and changes in relative intensity of the characteristic bands, were observed. The enhancement of the spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
160
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(183 citation statements)
references
References 47 publications
21
160
1
Order By: Relevance
“…The spectra are dominant with a 1 vibration modes at 1590 and 1078 cm −1 and the vibration mode at 390 cm −1 is assigned to one of the vibrational modes of the C-S bond, most likely the bending mode of the C-S bond. 34,35 And because a 1064 nm laser was used as the excitation source, a lesser extent of contribution of the Herzberg-Teller term is expected and thereby, the enhancement of b 2 modes is also less than that with the excitation in the visible region. 34,35 The EM mechanism is dominant though the CT mechanism cannot be neglected because of the apparent enhancement of b 2 modes at 1140 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra are dominant with a 1 vibration modes at 1590 and 1078 cm −1 and the vibration mode at 390 cm −1 is assigned to one of the vibrational modes of the C-S bond, most likely the bending mode of the C-S bond. 34,35 And because a 1064 nm laser was used as the excitation source, a lesser extent of contribution of the Herzberg-Teller term is expected and thereby, the enhancement of b 2 modes is also less than that with the excitation in the visible region. 34,35 The EM mechanism is dominant though the CT mechanism cannot be neglected because of the apparent enhancement of b 2 modes at 1140 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…34,35 And because a 1064 nm laser was used as the excitation source, a lesser extent of contribution of the Herzberg-Teller term is expected and thereby, the enhancement of b 2 modes is also less than that with the excitation in the visible region. 34,35 The EM mechanism is dominant though the CT mechanism cannot be neglected because of the apparent enhancement of b 2 modes at 1140 cm −1 . It has reported that metal nanoshells with shell layers consisting of metals with strong plasmon resonances exhibit a strong, plasmon-derived optical resonance, typically shifted to much longer wavelengths than the plasmon resonance of the corresponding solid metal nanosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The top electrode could be metal nanoclusters prepared by vacuum vapor deposition [1][2][3][4][5][6][7][8][9][10] or from a suspension of metal nanoparticles. [11][12][13][14] Previous studies have shown that vapor-deposited Au or Ag penetrates into the SAM and inserts into the thiol-Au bond at the Au/ SAM interface when it is vacuum-deposited on an alkanethiol SAM with a methyl end group. 2,3,[5][6][7] In contrast, when they are deposited on an alkanedithiol SAM with a thiol end group pointing up, metal nanoparticles are formed on top of the SAM.…”
Section: Introductionmentioning
confidence: 99%
“…Without selective detector, the Raman spectra only selected the lipid-and nucleotide-condensed regions from the others, which might lead to the misinterpretation if the healthy cells also have condensed organic organism; such as in the skin hole-close region shown in our experiment. Besides, no specific peaks would be applicable for a selective discrimination of BCC tissue from healthy tissue, which lead to long acquisition time for intraoperative diagnostic (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) h/mm 2 ) [7]. From all the results described above, only regions marked by A2, B2, C2 and D2 can be surely considered as the cancer areas, while A1, B1, C1 and D1 regions may assigned as the position of a hair-hole where the cell concentration also higher than others parts.…”
Section: Gold Nanoparticles Surface Modificationmentioning
confidence: 99%
“…Since the discovery of this surface-enhanced Raman (SER) scattering in 1974 [9], SER scattering has been recognized as a powerful technique for biomedical applications. The application of SER scattering has been studied in cancer detection [10][11][12], widely in molecular structure analysis [13][14][15][16]. For non-labeling agent probes, the Raman spectra were analyzed by measuring the intrinsic signals to distinguish between healthy and diseased regions [10,11].…”
Section: Introductionmentioning
confidence: 99%